EFFECT OF NANO-SiO2 PARTICLES ON PARTIAL DISCHARGE SIGNAL CHARACTERISTICS OF FR3 TRANSFORMER OIL (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
Liquid insulation for high voltage transformer applications based on natural esters derived from abundantly available vegetable oils are becoming popular in recent times. Since these natural ester based oils have environmental advantages and superior thermal performance, electrical utilities are slowly replacing the conventional mineral oils with natural ester based vegetable oils. FR3 oil, which is a soya based natural ester oil with superior dielectric and thermal characteristics, is becoming popular as an alternate insulating medium for high voltage transformers. With recent developments in nanotechnology field, it is possible to enhance the dielectric performance characteristics of natural ester based oils, which is a major constraint for high voltage transformer applications. However few research reports are only available in the area of nanofluids based on natural esters for high voltage insulation applications. In depth analysis and collection of large data base of insulation performance of natural ester based vegetable oils is important to improve the confidence level over nano-fluids based on natural esters. Considering these facts, in the present work, partial discharge characteristics of Â nano-SiO2 modified FR3 oil at different electrode configurations are investigated at different %wt filler concentrations. Important parameters such as partial discharge inception voltage, stable PD formation voltage, partial discharge amplitude at different voltage magnitude and PD signal frequency characteristics are evaluated. From the results, it is observed that the partial discharge performance of FR3 oil is significantly improved with the addition of nano-SiO2 filler. Since in recent times FR3 oil is commercially used in many transformers, these results will be useful for enhancing the dielectric strength of high voltage transformers.